Bilateral patellar tendon rupture following low-energy trauma in a young patient without predisposing risk factors. (August 2022) - Murphy, Suzanne M.; McAleese, Timothy; Elghobashy, Osama; Walsh, James
Abstract: We describe the case of a 25 year old male who presented with a bilateral patellar tendon ruptures without any of the identified risk factors for tendon injuries. Our patient is the youngest adult reported to date with confirmed bilateral, unprovoked, patellar tendon ruptures. We accompany our case with an up-to-date literature review on this topic. A degree of clinical suspicion is required for emergency room physicians as well as orthopaedic surgeons assessing such patients to avoid missing bilateral injuries. Point of care ultrasound may be utilised when there is doubt regarding the diagnosis. Prompt surgical management and a specific rehabilitation programme are both required to ensure maximum recovery of these patients.